2015
DOI: 10.1186/s13027-015-0010-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in E6 and E7 oncogenes of human papillomavirus Type 16 from Congolese cervical cancer isolates

Abstract: BackgroundThe molecular epidemiological studies showed that some variants of HPV-16, distributed geographically, would present a higher risk of causing cervical cancer. This study aimed to analyze nucleotide changes of HPV-16 E6 and E7 genomic regions from infected Southwestern Congolese women.MethodsDNA of twenty HPV-16 isolates was analyzed by amplifying the E6 and E7 genes using type-specific primers PCR and direct sequencing. The sequences obtained were aligned with the HPV-16 GenBank reference sequences.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
3
14
0
3
Order By: Relevance
“…In good agreement with previous reports [ 22 , 33 , 34 ], the current study showed that E7 region was strongly conserved as compared to E6. We found only one mutation A647G (N29S), which is common in Asia women.…”
Section: Discussionsupporting
confidence: 93%
“…In good agreement with previous reports [ 22 , 33 , 34 ], the current study showed that E7 region was strongly conserved as compared to E6. We found only one mutation A647G (N29S), which is common in Asia women.…”
Section: Discussionsupporting
confidence: 93%
“…Congo, Morocco, Romania, China). The mutation we found in our sample set # 5, however, was not described in any of the studies [ 17 25 ]. We therefore conclude that this mutation represents a very low frequency mutation and will thus not influence the clinical performance of the OncoE6 Test in the general population, since it is highly unlikely to find this same mutation in relevant numbers elsewhere.…”
Section: Discussionmentioning
confidence: 75%
“…Hasil ini mendukung penelitian yang telah dikerjakan sebelumnya mengenai identifikasi tipe-tipe HPV yang berasal dari kedua rumah sakit tersebut, dimana ditemukan 40,4% merupakan HPV tipe 18 dan 28,5% merupakan HPV tipe 16 [10]. Diperlukan penelitian lebih lanjut terhadap varian gen E7 HPV18 ini, karena beberapa penelitian menyebutkan bahwa varian yang berbeda dari gen E7 HPV18 dapat memberikan aktivitas onkogenik yang berbeda pula terhadap kanker serviks yang ditimbulkannya [11] sehingga nantinya bisa dirancang jenis vaksin yang sesuai untuk penderita kanker serviks di wilayah Sumbar dan Riau khususnya dan Indonesia pada umumya.…”
Section: Hasil Dan Diskusiunclassified